EFEKTIVITAS KOMUNIKASI BERKELANJUTAN BUDAYA JAWA (Studi Kasus dalam Bentuk Sapaan Antaranggota Keluarga) - Ngalimun Ngalimun (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2016)
This study aims to determine the position of communication in the form ofgreeting among members of the family, communication in the forms of greetingamong members of the family and the factors that led to the existence ofcommunication in the form of an assortment of greeting among members of thefamily. This study shows that the effectiveness of ongoing communication Javanesecultural forms and manifestations vary. Based completeness of its elements, greetingcommunication among members of the family can be divided into three, namelycommunication form of greeting that looks complete and incomplete, as well as theform of communication form of address is a combination of communication forms acomplete address and communication form of address is not complete.Based on the classification of meaning and means of communication betweenfamily members form of address can be the name of self, kin terms, paraban,knighted, adjective and poyokan transformation.While based on the factors thatinfluence communication among members of the family is a form of greeting theparticipants said, the intention said, the color of emotion, the second and the third,the tone of talk atmosphere, environment and infrastructure said said.